Integral program for the productive and environmental reconversion of livestock farming in Colombia (PIRPAG, as per its Spanish acronym) - Robledo, Pablo; Tapasco, Jeimar; Valencia Garcia, Jhon Brayan (2021)
The project seeks to evaluate options for livestock conversion in 5 municipalities prioritized for the reduction of greenhouse gas emissions. This proposes four large zones for the implementation of Sustainable Livestock pilots, carrying out activities in cooperation with various institutional actors and 80 livestock-raising families in an intervention area of 1.103 hectares in San Onofre (Sucre) in the humid Caribbean region; Dibulla (La Guajira) in the dry Caribbean region; El Carmen de Chucurí (Santander) in the Piedemonte del Magdalena Medio region and in Tame (Arauca) in the Piedemonte of Orinoco region.